Half Empty and Half Full? Women in Economics and the Rise in Gender-Related Research - Francisca M. Antman; Kirk Doran; Xuechao Qian; Bruce A. Weinberg (Institute of Labor Economics (IZA), 2024)
Using the EconLit dissertation database and large-scale algorithmic methods that identify author demographics from names, we investigate the connection between the gender of economics dissertators and dissertation topics. Despite stagnation in the share of women among economics Ph.D.s in recent years, there has been a remarkable rise in gender-related dissertations in economics over time and in many sub-fields. Women economists are significantly more likely to write gender-related dissertations and bring gender-related topics into a wide range of fields within economics. Men in economics have also substantially increased their interest in gender-related topics.
Keywords: I23; J16; O30; 330; economic research; gender; dissertation